SISTEM INFORMASI PENGELOLAAN SURAT MASUK DAN SURAT KELUAR PADA AKPOL SEMARANG BERBASIS WEB - SEFI RENANDO, FARERA; TRI HANDOKO, DRS.,M.KOM, WIDIYANTO (Information Technology and Telematics, 2018)
Abstract- Manual letter management system is to record in the ledger as a letter agenda book has not made the system of accuracy in Akpol Semarang become more efficient. Writing the disposition of incoming mail is rewriting the contents of the incoming mail in the incoming mailing agency. Actually, the two jobs can be done together in one job. Then also because of the lack of clarity of writing sometimes error in the numbering of the letter so that when one of the numbers will affect the next number. The purpose of this study is to build information systems management of incoming mail and outgoing mail on web-based Semarang Akpol that can facilitate the search and management of letters on the Akpol Semarang. System development method used in this research is Waterfall, system design using UML and system implementation using PHP and MySQL.The result of this research is the information management system of incoming mail and outgoing letter on the web-based Semarang Akpol can facilitate the management of incoming and outgoing mail in Akpol Semarang and facilitate the searching of incoming mail and outgoing mail on Akpol Semarang Keywords – Information System, Letter, Akpol Semarang, PHP, MySQLDAFTAR PUSTAKA Aditya, A.N, (2010) Jago PHP & MySQL Dalam Hitungan Menit, Dunia Komputer, Bekasi Barthos, B., (2009) Manajemen Kearsipan, Bumi Aksara. Jakarta Bibit, Sukadi, (2015) Sistem Pengelolaan Surat Masuk Dan Surat Keluar Terkomputerisasi Pada Unit Pelaksana Teknis (Upt) Sekolah Menengah Pertama (SMP) Negeri 1 Tegalombo, Skripsi, Universitas Surakarta Henderi (2008) Unified Modelling Language, Raharja Enrichment Centre (REC), Tangerang Latubessy, A., Ashari, A., (2012) Implementasi Basisdata Terdistribusi Pada Sistem Kenaikan Gaji Berkala Dinas Infokom Provinsi Maluku, Skripsi, Universitas Gajah Mada Yogyakarta Nugroho, A., (2011) Perancangan dan Implementasi Sistem Basis Data, Andi, Yogyakarta Poerwadarminta, W.J.S.,  (2006) Kamus Umum Bahasa Indonesia, Balai Pustaka, Jakarta Prasetyo, D.D, (2006) Administrasi Database Server MySQL, Elex Media Komputindo, Jakarta Syaban, R.M., Bunyamin, (2015) Pengembangan Sistem Informasi Pengelolaan Surat Masuk Dan Surat Keluar Berbasis Web Di Dinas Sosial Tenaga Kerja Dan Transmigrasi Kabupaten Garut Menggunakan Framework PHP, Skripsi, Sekolah Tinggi Teknologi Garut Whitten, J.L., (2004), Metode Desain dan Analisa Sistem, Andi Offset, Yogyakarta